Adapting the existential gratitude scale to turkish: a measure of gratitude in painful times - EKŞİ, HALİL (My University, 2022)
This study aims to adapt the Existential Gratitude Scale (Jens-Beken & Wong, 2019) to Turkish culture and to examine the scale’s psychometric properties in this respect. The study uses the convenience sampling method, and the sample consists of 286 participants between the ages of 18 to 53, of whom 212 (74.1%) are female and 74 (25.9%) are male. The structural validity of the scale has been examined using confirmatory factor analysis (CFA). The CFA results confirm the original EGS’ one-dimensional structure over a Turkish sample, and the scale has good fit indices (χ2 =94.655, df=34, χ2 /df =2.784, GFI=0.936, NFI=0.930, CFI=0.954, SRMR=0.0420, and RMSEA=0.079). The factor loadings range from .46 to .77. For the criterion validity, Pearson correlations were calculated for the EGS with the Short Gratitude, Resentment, and Appreciation Scale and Transpersonal Gratitude Scales, which resulted in significant positive correlations (respectively r=0.476 and r=0.579 at p= 05). The item-total correlation and comparison of the upper 27% and lower 27% groups were examined for the item analysis of the scale; these have revealed the EGS to possess satisfactory discriminating power. As a result of the reliability analysis, Cronbach’s alpha of internal consistency was calculated as .893. This study shows the EGS to be a valid and reliable tool useable in the context of Turkey for measuring individuals’ existential gratitude levels. The EGS can be a valuable tool for practitioners in mental health settings in developing appropriate interventions for individuals’ coping skills in celebrating adversity.

Bu çalışmada, Jens-Beken ve Wong (2019) tarafından geliştiren Varoluşsal Şükür Ölçeği’nin Türk kültürüne uyarlanması amaçlanmıştır. Bu kapsamda, ölçeğin psikometrik özellikleri incelenmiştir. Çalışmada kolay örnekleme yöntemi uygulanmıştır. Çalışmanın örneklemini 212’si kadın ( %74.1), 74’ü erkek (%25.9), yaşları 18 ile 53 arasında değişen 286 kişi oluşturmuştur. Yapı geçerliliği Doğrulayıcı Faktör Analizi (DFA) ile analiz edilmiştir. DFA sonuçları original ölçeğin tek faktörlü yapısını Türk örnekleminde doğrulamış ve iyi uyum değerleri göstermiştir (χ2 /df =2.784, GFI=0,936, NFI=0,930, CFI=0,954, SRMR=0,0420 ve RMSEA=0,079). Ölçeğin factor yükleri .46 ile .77 arasında değişmiştir. Ölçüt geçerliliği için ölçeğin Minnettarlık Gücenme ve Takdir Ölçeği Gözden Geçirilmiş Kısa Formu (K-MGTÖ) ve Manevi Şükür Ölçeği arasındaki Pearson Korelasyon Katsayısı hesaplanmış ve pozitif yönde anlamlı sonuçlar çıkmıştır (r=0,476, r=0,579, p= .05). Ölçeğin madde analizi için yapılan madde-toplam puan korelasyonu ve %27 alt-üst grup karşılaştırması sonucunda ölçeğin iyi bir ayırt edicilik düzeyine sahip olduğu görülmüştür. Güvenirlik analizi sonucuna göre, Cronbach iç tutarlık katsayısı .893 olarak hesaplanmıştır. Bu çalışma, Varoluşsal Şükür Ölçeği’nin Türkçe versiyonunun kişilerin varoluşsal şükür düzeyini ölçmede geçerli ve güvenilir bir ölçme aracı olduğunu göstermiştir. Bu ölçek, ruh sağlığı alanında çalışan uygulamacıların, kişilerin zorlukları daha iyi karşılamak için baş etme becerilerini geliştirecek uygun müdahaleler tasarlaması için değerli bir araç olabilir.